At skrive fra torturbødlens stol. Om forfatterens valg og metoder i Gaute Heivolls "Himmelarkivet" - Simonhjell, Nora (Passage - Tidsskrift for litteratur og kritik, 2011)
Nora Simonhjell: “Writing From the Chair of the Torturer” The Norwegian author Gaute Heivolls novel Himmelarkivet [The Archive in Heaven], is both a documentary novel and a reflection upon the creative writing process itself. In January 1945 Louis Hogganvik was arrested by the Gestapo. He was tortured, and ended up comitting suicide. Hogganvik’s destiny has been silenced both in the family history and in the local community, until Heivoll started to write this novel. At one point he is back in the torture chamber, and ends up sitting in the same chair as the man in charge for the torture. How does this bodily repetition affect the contemporary young author’s narrative strategies?